A breath of fresh Eyre : intertextual and intermedial reworkings of Jane Eyre - Rubik, Margarete, 1950-; Mettinger-Schartmann, Elke (Internationale Forschungen zur allgemeinen und vergleichenden Literaturwissenschaft, 2007)
Ever since its publication in 1847 Jane Eyre - one of the most popular English novels of all time - has fascinated scholars and a wide reading public alike and has proved a source of inspiration to successive generations of creative writers and artists. There is hardly any other hypotext that has been re-worked in so many adaptations for stage and screen, has inspired so many painters and musicians, and has been so often imitated, re-written, parodied or extended by prequels and sequels. New versions in turn refer to and revise older rewritings or take up suggestions from Brontë scholarship, c.